Application of FTIR Spectroscopy and Chemometrics for the Prediction of Radical Scavenging Activities of Fish oils - Arif Nur Ikhsan; Abdul Rohman; Anggita Rosiana Putri; Fella Syifa; Mabrurotul Mustafidah; Ronny Martien (Universitas Gadjah Mada, 2021)
Patin fish (Pangasius micronemus), Gabus fish (Channa striata) and Bandeng fish (Chanos chanos) are the freshwater fish that are widely cultivated in Indonesia, fish oils extracted are believed has antioxidant activity. The goals of this study was (1) determining antioxidant activities using radical scavenging activity (RSA) 2,2'-diphenyl-1-picrylhydrazil (DPPH), (2) classifying of fish oil from different species and extraction method using principal component analysis (PCA) and cluster analysis (CA) and predicting antioxidant activities of fish oil from different species and extraction method using FTIR spectroscopy combined principal component regression (PCR) and partial least square regression (PLS). The results exhibit radical scavenging activity (RSA) of patin fish flesh oil (maceration dried samples using chloroform) giving highest RSA (23.57 ± 0.14). PCA and CA succesfully classify of fish oil from different species and extraction based on PC1 - PC2 score plots and grouping into 4 groups based on dendogram. Optimal PCR method were obtained from second derivative spectra at wavenumbers region 1440 - 1741 cm-1 with highest R2 (0,9794), lowest RMSEC (0,737), and lowest RMSEP (0,927) in calibration and validation models. From this study we can concluded FTIR spectroscopy combined with chemometrics can be classifying and predicting antioxidant activity of fish oil from different species and extraction method successfully.